The Role of Co-Workers' Solidarity as an Antecedent of Incivility and Deviant Behavior in Organizations. Issue 8 (2nd August 2016) - Itzkovich, Yariv; Heilbrunn, Sibylle
ABSTRACT: Drawing on the social exchange theory this study assesses the relationship between co-workers' solidarity as an antecedent of incivility and deviant behavior. More specifically we hypothesize that reduced co-workers' solidarity will increase not only incivility but also deviant behaviors of employees. An additional hypothesis predicts that incivility will enhance co-workers' deviant behavior. Data was collected in 15 organizations of various types using an online questionnaire in 2014. We analyze the data using structural equation modeling. Our findings reveal interrelationships between all three variables. Co-workers' solidarity reduces uncivil and deviant behaviors of employees, whereas incivility increases organizational deviance. Moreover, we found that the explained variance of property deviance by incivility was twice as high compared to production deviance.